Recombinant antigen 5 from Polybia paulista wasp venom (Hymenoptera, Vespidae): Antigen-specific antibody production and functional profile of CD4+ T cells in the immune response - Assugeni, Isabela Oliveira Sandrini [UNESP] (2023)
Polybia paulista is a neotropical social wasp related to severe accidents and allergic reactions cases, including anaphylaxis, in southeastern Brazil. Antigen 5 (Poly p 5) is a major allergenic protein from its venom with potential use for component-resolved diagnostic. Therefore, the previous characterization of the immune response profile triggered by Poly p 5 should be evaluated. Recombinant Poly p 5 (rPoly p 5) was used to sensitize BALB/c mice with six weekly intradermal doses, and the specific antibody production and the functional profile of CD4+ T cells were assessed. rPoly p 5 induced the production of specific immunoglobulins (sIg) sIgE, sIgG1 and sIgG2a, which could recognize natural Poly p 5 presented in the venom of four different wasp species. rPoly p 5 stimulated in vitro the CD4+ T cells from immunized mice, which showed a significant proliferative response. These antigen-specific CD4+T cells produced IFN-γ and IL-17A cytokines and increased ROR-γT transcription factor expression. No differences between the control group and sensitized mice were found in IL-4 production and GATA-3 and T-bet expression. Interestingly, increased CD25+FoxP3+ regulatory T cells (Tregs) frequency was observed in the splenocyte cell cultures from rPoly p 5 immunized mice after the in vitro stimulation with both P. paulista venom extract and rPoly p 5. Here we showed that rPoly p 5 induces antigen-specific antibodies capable of recognizing Antigen 5 in the venom of four wasp species and modulates antigen-specific CD4+ T cells to IFN-γ production response associated with a Th17 profile in sensitized mice. These findings emphasize the potential use of rPoly p 5 as an essential source of a major wasp allergen with significant immunological properties.